2017
DOI: 10.1557/jmr.2017.60
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, microstructure and mechanical properties of (Ti,Mo)Al/Al2O3in situ composites by reactive hot pressing

Abstract: composites were successfully synthesized utilizing in situ reactive hot pressing method with Ti, Al, and MoO 3 powders as starting materials. A possible synthesis mechanism was proposed to explain the formation of (Ti,Mo)Al/Al 2 O 3 composites. The investigation results indicate a probable reaction process that molten Al reacted with MoO 3 to form Al 2 O 3 and Mo, and the TiAl matrix grains were refined increasingly by Al 2 O 3 with the addition of MoO 3 increased, accompanying with a small quantity of Mo cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Cr 2 AlC containing up to 20 vol% Al 2 O 3 particles were processed by in-situ reaction of Cr 3 C 2 , Cr, Al, and Cr 2 O 3 powders in HP at 1400°C. 204 Hardness and flexural strength increase continuously with the alumina content, meanwhile the fracture toughness increases with contents up to 11 vol% Al 2 O 3 followed by a decrease for higher alumina contents. This strategy is simple and controls properly the second phase content, but unfortunately does not tailor the morphology of the particles.…”
Section: Max Phase Compositesmentioning
confidence: 90%
“…Cr 2 AlC containing up to 20 vol% Al 2 O 3 particles were processed by in-situ reaction of Cr 3 C 2 , Cr, Al, and Cr 2 O 3 powders in HP at 1400°C. 204 Hardness and flexural strength increase continuously with the alumina content, meanwhile the fracture toughness increases with contents up to 11 vol% Al 2 O 3 followed by a decrease for higher alumina contents. This strategy is simple and controls properly the second phase content, but unfortunately does not tailor the morphology of the particles.…”
Section: Max Phase Compositesmentioning
confidence: 90%
“…Moreover, incorporation of a second phase is also an attractive method to effectively improve the mechanical properties of MAX phases [22][23][24]. Al 2 O 3 has been commonly selected as a reinforcement for Ti 2 AlC-and Ti 3 AlC 2 -based MAX phases [16,20,[25][26][27][28], owing to its high hardness (18 GPa), high elastic modulus (386 GPa), and almost similar thermal expansion coefficient (8.3×10 6 K 1 ) to MAX phase (Ti 2 AlC (8.2×10 6 K 1 ) or Ti 3 AlC 2 (9.0×10 6 K 1 ) in particular). Wu et al [29] reported that incorporation of Al 2 O 3 into Ti 3 AlC 2 matrix improved its wear resistance, because Al 2 O 3 particles acquired a part of load and restrained large-scale deformation and microfracture of Ti 3 AlC 2 .…”
Section: Introduction mentioning
confidence: 99%
“…Furthermore, a combining process of tape casting and reactive hot pressing (RHP) was an in-situ way to fabricate dense laminated ceramics with advantages of low energy requirement, high density and strong bonding interfaces [28]. However, to the best of our knowledge, few studies on the dynamic compressive characteristics of laminated ceramics with soft and hard interbedded dense layers have been reported, and the dynamic fracture mechanism has not been understood.…”
Section: Introductionmentioning
confidence: 99%